Legal Certainty of Marriage Agreements that Were Not Registered After the Constitutional Court Decision Number 69/Puu-Xii/2015 - Marhongki, Hendri; Hasana, Dahniarti (Jurnal Konstatering, 2025)
The Marriage Law has facilitated couples to make marriage agreements. Before the Constitutional Court Decision No. 69/PUU–XII/2015, the public was more familiar with it as a prenuptial agreement. Basically, the creation of a marriage agreement regulates the assets owned by each husband and/or wife before the marriage takes place, during the implementation of the marriage relationship, the division of responsibilities for paying debt agreements, the transfer of assets, and the division of assets in the event of a divorce. 2 As stated in Article 29 paragraph (1) of the Marriage Law which states that both parties (husband and wife) with mutual consent can enter into a written marriage agreement which agreement will then be ratified by a marriage registrar. The marriage agreement will also apply to third parties if there is a connection found in the contents of the agreement. The research method used is normative legal research. The approach method used in this research is a case study approach and a statutory approach. Data analysis is an activity in research that takes the form of conducting a study of the results of data processing. Before the Constitutional Court Decision Number 69/PUU-XIII/2015, the legal status of a marriage agreement made by a husband and wife after the marriage took place was bound by the provisions of Article 29 of the Marriage Law, namely invalid and non-binding, unless based on a court decision requested by the husband and wife before making the marriage agreement. So without a court decision, the marriage agreement made during the marriage bond is invalid and non-binding. But after the Constitutional Court Decision Number 69/PUU-XIII/2015, the status of a marriage agreement made by a husband and wife during the marriage bond is valid and binding, both to both parties, as well as to third parties as long as the third party is involved.